Transcriptomic analysis of the symbiotic responsivity trait in pea (Pisum sativum L.) - D. O. Kuzmina; E. A. Zorin; A. S. Sulima; D. A. Romanyuk; M. L. Gordon; A. I. Zhernako; O. A. Kulaeva; G. A. Akhtemova; O. . Shtark; I. A. Tikhonovich; V. A. Zhukov (Вавиловский журнал генетики и селекции, 2025)
Pea (Pisum sativum L.) is an important crop culture and a model object for studying the molecular genetic bases of nitrogen-fixing symbiosis and arbuscular mycorrhiza (AM). Pea genotypes with high and low responsivity to inoculation with nodule bacteria (rhizobia) and AM fungi have been described: the ‘responsive’ genotypes demonstrate an increase in seed weight under inoculation, while ‘non-responsive’ ones do not show such a reaction. In order to get insight into the molecular genetic mechanisms underlying the symbiotic responsivity, a transcriptomic analysis of whole root systems of pea plants of the ‘responsive’ genotype k-8274 (cv. Vendevil, France) and ‘non-responsive’ genotype k-3358 (unnamed cultivar, Saratov region, Russia) grown in soil without inoculation (control) and inoculated either with rhizobia (single inoculation) or with rhizobia together with AM fungi (double inoculation) was performed. It was shown that the ‘responsive’ genotype, indeed, demonstrated a pronounced transcriptomic response to single and double inoculation, in contrast to the ‘non-responsive’ genotype. In k-8274, single inoculation led to specific up-regulation of genes related to catabolism of polyamines, lipid metabolism, and jasmonic acid and salicylic acid signaling. Under double inoculation, the specifically up-regulated genes in k-8274 were related to arbuscular mycorrhiza infection, and the down-regulated genes were related to nodulation. This fact matches the phenotype of the plants: the number of nodules was lower in k-8274 under double inoculation as compared to the control. Thus, strict control over the nodule number may be one of the mechanisms underlying the symbiotic responsivity of pea. Finally, a comparison of expression profiles in k-8274 and k-3358 roots under double inoculation also allowed us to identify the transcriptomic signatures characteristic of the symbiotically responsive genotype. Further work will be focused on validation of these transcriptomic markers of the symbiotic responsivity trait in pea.